Labelling the debate: a thematic analysis of alcohol industry submissions to the EU consultation on alcohol health warnings in Ireland - Éadaoin Cott; Jelena Dunaiceva; Philippa White; Runa Annasdotter Neely; Matthew Lesch (Globalization and Health)
Abstract Background Building on the success of tobacco health warning labels, EU Member States and institutions are increasingly considering similar requirements for alcohol products. While industry responses to pricing and availability policies have been widely studied, their framing of Alcohol Health Warning Labels (AHWLs) as a policy solution remains comparatively underexplored. This paper examines how alcohol industry stakeholders responded to the EU notification process for Ireland’s proposed alcohol labelling regulations, introduced under Ireland’s Public Health (Alcohol) Act 2018. Methods This paper analyses 16 submissions from alcohol industry actors to the European Commission regarding Ireland’s proposed alcohol warning label regulations. Qualitative methods, specifically thematic analysis, were used to examine industry arguments. The research team first reviewed five submissions to inductively develop a codebook, which was then applied to the remaining submissions, with new codes added as necessary. Two team members independently coded each submission, and thematic content was refined through team discussion. Results Alcohol industry arguments against AHWLs fall into four main themes: lack of evidence supporting the content of health warning labels and their broader use, negative trade and economic impacts of AHWLs, potential risks to EU governance posed by Ireland’s labels, and the industry’s self-positioning as responsible actors committed to public health. In addition, we identify novel industry strategies related to the intricacies of AHWLs, including a heightened focus on wording and language, coordination of activities across multiple governance levels, and tailored framing to suit the institutional context. Conclusions Alcohol industry actors employ arguments similar to those seen in other policy debates, which continue to pose a significant barrier to evidence-based alcohol policymaking. The analysis suggests that industry actors can strategically adapt their arguments to varying institutional settings and policy instruments, demonstrating their political dexterity and reinforcing the barriers to policy progress. These findings highlight the need for further research into the alcohol industry’s influence and provide insights for jurisdictions considering labelling legislation.